CPP UV visbreaking protective film

By using a combination of transparent polyester release film, UV detachable adhesive and CPP film in the UV detachable protective film, the problem of strong adhesion ability of the UV detachable protective film during peeling in the prior art is solved, and the effect of high viscosity before cutting and low viscosity after peeling is achieved, which facilitates the peeling of the finished product.

CN119955423APending Publication Date: 2025-05-09WAISI NEW MATERIALS TAIZHOU CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510002567.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

In the prior art, the UV adhesive reducing protective film has strong adhesive ability during peeling, resulting in less peeling and easy glue retention.

Method used

A CPP UV adhesive reducing protective film is adopted, including transparent polyester release film, UV debonding adhesive and CPP film. The UV debonding adhesive is bonded to the CPP film and is located at the upper end of the CPP film. The transparent polyester release film is bonded to the UV debonding adhesive and is located at the upper end of the UV debonding adhesive.

Benefits of technology

It achieves high viscosity before cutting, ensuring the completion of cutting and cleaning processes; UV irradiation after cutting, low viscosity, which facilitates the peeling of finished products, has flexibility and certain strength, ensuring the fitting and peeling efficiency, beautiful appearance, stable structure and excellent processability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119955423A_ABST
    Figure CN119955423A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of protective films, and particularly discloses a CPP UV visbreaking protective film which comprises a transparent polyester release film, a UV visbreaking adhesive and a CPP film, the UV visbreaking adhesive is bonded with the CPP film and located at the upper end of the CPP film, and the transparent polyester release film is bonded with the UV visbreaking adhesive and located at the upper end of the UV visbreaking adhesive. The modified UV visbreaking polyacrylate pressure-sensitive adhesive has high viscidity before cutting a pasted object, ensures completion of cutting and cleaning procedures, is subjected to UV irradiation after cutting, has low viscidity, is convenient for stripping a finished product, has flexibility and certain strength, ensures the attaching property before cutting and the stripping efficiency and appearance attractiveness of the finished product after later cutting, and is stable in structure and excellent in processability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective films, in particular to a CPP UV viscosity-reducing protective film. Background Art

[0002] At present, with the demand for thinner electronic products, CPP thin UV anti-viscosity protective film generally includes a release layer, a substrate layer and a modified UV anti-viscosity polyacrylate pressure-sensitive adhesive layer. It is a multi-layer structure. The stability of the interlayer structure and the physical properties of the modified UV anti-viscosity polyacrylate pressure-sensitive adhesive layer directly affect the performance of the UV anti-viscosity protective film.

[0003] In the prior art, during the LED bracket cutting process, when the bracket is cut and cleaned, in order to improve the bracket cutting yield, a UV anti-sticking film for LED bracket cutting is usually used.

[0004] However, in the prior art, the adhesive ability is strong during use, which makes it difficult to peel off the protective film and easily leaves glue. Summary of the invention

[0005] The object of the present invention is to provide a CPP UV anti-viscosity protective film, aiming to solve the technical problem in the prior art that the strong adhesive ability during use makes it difficult to peel off the protective film and easily leaves adhesive when peeling off the protective film.

[0006] To achieve the above purpose, the present invention adopts a CPP UV anti-viscosity protective film, which includes a transparent polyester release film, a UV anti-viscosity adhesive and a CPP film, wherein the UV anti-viscosity adhesive is bonded to the CPP film and is located at the upper end of the CPP film, and the transparent polyester release film is bonded to the UV anti-viscosity adhesive and is located at the upper end of the UV anti-viscosity adhesive.

[0007] The CPP film is composed of polypropylene resin, propylene monomer, comonomer, catalyst, auxiliary raw materials and coloring carbon powder.

[0008] The catalyst is any one or more combinations of Ziegler-Natta catalyst, metallocene catalyst, late transition metal catalyst, chromium catalyst and non-metallocene single active center catalyst.

[0009] The auxiliary raw materials include antioxidants, stabilizers, charge regulators, antistatic agents and anti-caking agents.

[0010] The antioxidant is any one or more combinations of N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,1,3-tris[5-(tert-butyl)-4-hydroxy-2-methylphenyl]butane, diethylenethiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], dioctadecyl pentaerythritol bisphosphite, and N,N'-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)propylenediamine.

[0011] The stabilizer is any one or more combinations of light stabilizer, surfactant, inorganic filler, polyacrylonitrile, epoxy resin, dimethylacetamide and oxidized cellulose.

[0012] The charge regulator is any one or more combinations of 1,1'-binaphthol and chromium lactate, polyhydroxy aromatic acid, quaternary ammonium salts, tert-butyl salicylic acid metal complex, acetylated boron metal complex, azo metal complex, and zirconium compound.

[0013] The UV debonding adhesive is composed of an acrylic pressure-sensitive adhesive resin, an oligomer, a multifunctional monomer, a crosslinking agent and a photoinitiator.

[0014] Wherein, the multifunctional monomer is any one or more combinations of TMP3POTA, DPHA, PET4A and IBOA.

[0015] The cross-linking agent is any one or more combinations of cyanate cross-linking agents, epoxy cross-linking agents, and metal chelates.

[0016] The CPP UV viscosity-reducing protective film of the present invention has the following beneficial effects: the modified UV viscosity-reducing polyacrylate pressure-sensitive adhesive has high viscosity to the adhered object before cutting, ensuring the completion of the cutting and cleaning processes, UV irradiation after cutting, low viscosity, easy peeling of the finished product, flexibility and certain strength, ensuring the adherence before cutting and the peeling efficiency and appearance of the finished product after the later cutting, stable structure and excellent processability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 It is a structural schematic diagram of a CPP UV viscosity-reducing protective film of the present invention.

[0019] 1- Transparent polyester release film, 2- UV debonding adhesive, 3- CPP film. DETAILED DESCRIPTION

[0020] See also Figure 1 The present invention provides a CPP UV anti-viscosity protective film, comprising a transparent polyester release film 1, a UV anti-viscosity adhesive 2 and a CPP film 3, wherein the UV anti-viscosity adhesive 2 is bonded to the CPP film 3 and is located at the upper end of the CPP film 3, and the transparent polyester release film 1 is bonded to the UV anti-viscosity adhesive 2 and is located at the upper end of the UV anti-viscosity adhesive 2.

[0021] In this embodiment, the modified UV viscosity-reducing polyacrylate pressure-sensitive adhesive has high viscosity to the object before cutting, ensuring the completion of the cutting and cleaning processes. After cutting, it is UV-irradiated and has low viscosity, which is convenient for peeling off the finished product. It has flexibility and certain strength, ensuring the adhesion before cutting and the peeling efficiency and appearance of the finished product after the later cutting. It has a stable structure and excellent processability.

[0022] Furthermore, the CPP film 3 is composed of polypropylene resin, propylene monomer, comonomer, catalyst, auxiliary raw materials and coloring carbon powder.

[0023] In this embodiment, the polypropylene resin can be a homopolymer or a copolymer, wherein the copolymer still has good impact strength and heat sealing properties at low temperatures; propylene is the basis for the synthesis of polypropylene, and its purity and quality directly affect the performance of the final polypropylene product; when producing copolymer polypropylene, in addition to propylene monomer, ethylene is also added as a comonomer to change the properties of polypropylene and improve the impact resistance; colored carbon powder is used to form CPP UV viscosity-reducing protective films of different colors.

[0024] Furthermore, the catalyst is any one or more combinations of Ziegler-Natta catalysts, metallocene catalysts, late transition metal catalysts, chromium catalysts, and non-metallocene single-active-site catalysts.

[0025] In this embodiment, the Ziegler-Natta catalyst is composed of a transition metal compound and an organic metal compound; the metallocene catalyst has the characteristics of good polymerization activity, a single active center, strong copolymerization ability, and good directional coordination ability, and can produce polyolefin products with various properties; the late transition metal catalyst has good activity, a single active center, and weak electrophilic properties; different catalyst selections can determine the rate and efficiency of the polymerization reaction, and affect the molecular structure, molecular weight distribution and performance characteristics of the final polymer.

[0026] Furthermore, the auxiliary raw materials include antioxidants, stabilizers, charge regulators, antistatic agents and anti-caking agents.

[0027] In this embodiment, the processing and preparation of the CPP film 3 is assisted by auxiliary raw materials, so that the functionality of the CPP film 3 is enhanced.

[0028] Furthermore, the antioxidant is any one or more combinations of N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,1,3-tris[5-(tert-butyl)-4-hydroxy-2-methylphenyl]butane, diethylenethiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], dioctadecyl pentaerythritol bisphosphite, and N,N'-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)propylenediamine.

[0029] In this embodiment, the antioxidant provides thermal stability and anti-oxidation protection for the CPP film 3 through different chemical structures and action mechanisms, thereby extending the service life of the material and maintaining its performance.

[0030] Furthermore, the stabilizer is any one or more combinations of light stabilizers, surfactants, inorganic fillers, polyacrylonitrile, epoxy resins, dimethylacetamide, and oxidized cellulose.

[0031] In this embodiment, the stabilizer provides thermal stability, weather resistance and chemical resistance to the CPP film 3 through different chemical structures and action mechanisms, thereby extending the service life of the material and maintaining its performance.

[0032] Furthermore, the charge regulator is any one or more combinations of 1,1'-binaphthol and chromium lactate, polyhydroxy aromatic acid, quaternary ammonium salts, tert-butyl salicylic acid metal complex, acetylated boron metal complex, azo metal complex, and zirconium compound.

[0033] In this embodiment, by adjusting the charge of the CPP film 3, it can be more suitable for use in electronic devices.

[0034] Furthermore, the UV debonding adhesive 2 is composed of an acrylic pressure-sensitive adhesive resin, an oligomer, a multifunctional monomer, a cross-linking agent and a photoinitiator.

[0035] In this embodiment, the adhesive force is strong during use, and in the later peeling process, the adhesive force is weakened to facilitate peeling and ensure that the LED bracket cutting process is successfully completed.

[0036] Furthermore, the multifunctional monomer is any one or more combinations of TMP3POTA, DPHA, PET4A and IBOA.

[0037] In this embodiment, the material properties are improved: the introduction of multifunctional monomers can enhance the compatibility between nano-silica and polyester film, reduce the agglomeration of nano-silica, thereby better exerting the mechanical and optical properties of nano-silica and improving the light transmittance of polyester release film; improve dispersibility: multifunctional monomers can react with the surface of nano-silica to form chemical bonds, thereby improving the dispersibility of nano-silica in the polyester matrix, reducing agglomeration, and improving the uniformity and stability of the material; enhance the toughening effect: the addition of multifunctional monomers can increase the nominal strain at break, tensile strength and elastic modulus of the composite material, thereby enhancing the toughening effect; improve weather resistance and heat resistance: the introduction of multifunctional monomers can enhance the weather resistance and heat resistance of polyester release film, making it stable under high temperature environment and suitable for extreme High temperature application; Improve processing performance: Multifunctional monomers can be used as processing aids to reduce resin viscosity, improve processability, achieve uniform diffusion of fillers in polymer materials, improve processing performance, and enhance product surface quality; Improve cohesive energy and high temperature resistance: Multifunctional monomers introduce strong rigid groups into the molecule to increase cohesive energy and thus improve high temperature resistance; Regulate crosslinking density: Polyurethane prepolymers modified with toughening agents can regulate crosslinking density to further improve material performance; Improve the overall quality of composite materials: The introduction of multifunctional monomers can enhance weather resistance and improve the overall quality of finished products; Enhance physical crosslinking: Nanoparticles and matrix molecular chains play a role of physical crosslinking through the interface layer. When the material is subjected to tensile stress, the crosslinking points can play a role in uniformly distributing stress, thereby achieving an enhanced effect.

[0038] Furthermore, the cross-linking agent is any one or more combinations of cyanate cross-linking agents, epoxy cross-linking agents, and metal chelates.

[0039] In this embodiment, the heat resistance is improved: the copolymerization of cyanate crosslinking agent and epoxy resin can greatly improve the heat resistance of the resin. The triazine ring structure generated by the self-polymerization of cyanate resin is regular, highly crystallinity, and has high heat resistance; the dielectric properties are improved: the addition of cyanate crosslinking agent can reduce the dielectric constant and dielectric loss of epoxy resin, because the triazine ring structure is insensitive to polarization relaxation under the action of an external electric field; the dimensional stability is enhanced: the addition of cyanate crosslinking agent improves the dimensional stability of epoxy resin, because the crosslinked network structure of cyanate resin is relatively stable; the glass transition temperature (Tg) is increased: with the increase of cyanate content, the Tg of the co-cured product increases, because the increase of triazine ring structure makes the system structure more stable; the mechanical properties are improved: although the addition of cyanate will reduce the impact strength in the initial stage, with the increase of cyanate, the generated oxazolinone heterocyclic structure reduces the crosslinking density of the triazine ring and improves the toughness of the cured resin; the resin cost is reduced: by appropriately adjusting the ratio of cyanate to epoxy resin, a resin material with relatively good comprehensive performance can be obtained, while reducing the use cost of pure cyanate.

[0040] Furthermore, the transparent polyester release film 1 is composed of polyethylene terephthalate, modified nano-silicon dioxide masterbatch, barium sulfate, nucleating crystallization agent masterbatch and release agent raw materials.

[0041] Furthermore, the release agent raw materials include polyvinyl alcohol, modified nano-silicon dioxide, an inhibitor, a release regulator, a silane coupling agent and deionized water.

[0042] In this embodiment, the light transmittance is improved and the haze is reduced: adding modified nano-silica masterbatch to the base polyester film can increase the light transmittance of the polyester release film; at the same time, by adding nucleating crystallization agent masterbatch, the number of crystal nuclei can be increased, the spherulites can be refined and uniform, the light scattering degree can be reduced, the haze value can be reduced, and the transparency of the material can be increased, thereby further improving the light transmittance of the surface;

[0043] Enhance toughness and reduce residual rate: Add modified nano-silicon dioxide ions to the release agent and introduce a network Si-O-Si structure, which enhances the toughness of the release agent after film formation, reduces the residual rate of the release agent after film peeling, improves the transparency, brightness and whiteness of the release film, and makes the surface of the release film smooth and flat;

[0044] Improve compatibility and reduce agglomeration: Use silane coupling agent to modify nano-silica, reduce the number of hydroxyl groups on its surface, change it from hydrophilic to hydrophobic, improve the compatibility between nano-silica and organic matter, reduce the agglomeration of nano-silica, so as to better exert the mechanical and optical properties of nano-silica and improve the light transmittance of polyester release film;

[0045] Improve optical and mechanical properties: The addition of nucleating crystallizing agents, including DBS nucleating agent and calcium stearate, can improve the crystallinity of the polyester release film, making it uniform and dense, greatly improving the optical and mechanical properties, and improving the haze of the polyester release film;

[0046] Improve surface smoothness: Barium sulfate, as an optical opening masterbatch, can effectively play a connecting role and has little effect on the transmittance and haze of the polyester release film, which helps to improve the surface smoothness;

[0047] Environmentally friendly and harmless to human body: The catalyst used is one or a mixture of two or more of antimony catalysts, titanium catalysts, aluminum catalysts, germanium catalysts, and zinc catalysts. It can be a non-antimony catalyst or a compound with an antimony catalyst. It has high catalytic efficiency, can reduce the introduction of metal ions, is environmentally friendly, and harmless to human body.

[0048] Simplify the process and improve efficiency: Using ethylene glycol as the medium, the particle size, morphology and dispersion performance of the opening agent can be controlled through the sol-seed method, which solves the problem of inorganic particles agglomerating again due to grinding and dispersion, and simplifies the process and improves efficiency.

[0049] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A CPP UV anti-viscosity protective film, characterized in that: The invention comprises a transparent polyester release film, a UV debonding adhesive and a CPP film, wherein the UV debonding adhesive is bonded to the CPP film and is located at the upper end of the CPP film, and the transparent polyester release film is bonded to the UV debonding adhesive and is located at the upper end of the UV debonding adhesive.

2. A CPP UV anti-viscosity protective film as claimed in claim 1, characterized in that: The CPP film is composed of polypropylene resin, propylene monomer, comonomer, catalyst, auxiliary raw materials and coloring carbon powder.

3. A CPP UV anti-viscosity protective film as claimed in claim 2, characterized in that: The catalyst is any one or more combinations of Ziegler-Natta catalyst, metallocene catalyst, late transition metal catalyst, chromium catalyst and non-metallocene single active center catalyst.

4. A CPP UV anti-viscosity protective film as claimed in claim 2, characterized in that: The auxiliary raw materials include antioxidants, stabilizers, charge regulators, antistatic agents and anti-caking agents.

5. A CPP UV viscosity-reducing protective film as claimed in claim 4, characterized in that: The antioxidant is any one or more combinations of N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,1,3-tris[5-(tert-butyl)-4-hydroxy-2-methylphenyl]butane, diethylenethiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], dioctadecyl pentaerythritol bisphosphite, and N,N'-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)propylenediamine.

6. A CPP UV anti-viscosity protective film as claimed in claim 4, characterized in that: The stabilizer is any one or more combinations of light stabilizers, surfactants, inorganic fillers, polyacrylonitrile, epoxy resins, dimethylacetamide, and oxidized cellulose.

7. A CPP UV anti-viscosity protective film as claimed in claim 4, characterized in that: The charge regulator is any one or more combinations of 1,1'-binaphthol and chromium lactate, polyhydroxy aromatic acid, quaternary ammonium salts, tert-butyl salicylic acid metal complex, acetylated boron metal complex, azo metal complex, and zirconium compound.

8. The CPP UV anti-viscosity protective film according to claim 1, characterized in that: The UV debonding adhesive is composed of acrylic pressure-sensitive adhesive resin, oligomer, multifunctional monomer, crosslinking agent and photoinitiator.

9. A CPP UV anti-viscosity protective film as claimed in claim 8, characterized in that: The multifunctional monomer is any one or more combinations of TMP3POTA, DPHA, PET4A and IBOA.

10. A CPP UV anti-viscosity protective film as claimed in claim 8, characterized in that: The cross-linking agent is any one or more combinations of cyanate cross-linking agents, epoxy cross-linking agents, and metal chelates.